2007
DOI: 10.1111/j.1365-2710.2007.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of serum flecainide level on control of atrial fibrillation in a case treated with cardiac resynchronization therapy

Abstract: A 72-year-old male patient with dilated cardiomyopathy was treated with oral flecainide (100 mg/day) for persistent atrial fibrillation (AF) that could not be converted to sinus rhythm by electrical cardioversion. Initiation of flecainide treatment provided sinus rhythm without prolongation of QRS and QTc, bradycardia and first-degree atrioventricular block at a serum flecainide level of 438 ng/mL. Then, he received cardiac resynchronization therapy (CRT). Dose reduction to 50 mg/day because of stabilization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We previously reported that the serum flecainide concentration should be maintained at ≥300 ng/mL to control the paroxysms of supraventricular tachyarrhythmias [21][22][23]. The recommended serum flecainide concentration in Hap B carriers, however, is likely to be ≥200 ng/mL because the cumulative efficacy rate at around 200 ng/mL was similar to that at 300 ng/mL in the HapA homozygotes (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We previously reported that the serum flecainide concentration should be maintained at ≥300 ng/mL to control the paroxysms of supraventricular tachyarrhythmias [21][22][23]. The recommended serum flecainide concentration in Hap B carriers, however, is likely to be ≥200 ng/mL because the cumulative efficacy rate at around 200 ng/mL was similar to that at 300 ng/mL in the HapA homozygotes (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Tachyarrhythmias were well controlled in 63.0% of the HapB carriers and 51.6% of the HapA homozygotes; this difference was not significant (P = 0.18; Table 2). The influence of the SCN5A promoter haplotype on the anti-arrhythmic efficacy of flecainide was compared between the patients with serum flecainide concentrations <300 ng/mL and ≥300 ng/mL according to the previous reports [21][22][23]. The HapB carriers achieved clinically relevant flecainide efficacy more frequently (68.8%) when the serum flecainide concentrations were <300 ng/mL, compared with the HapA homozygotes (42.9%; P = 0.022; Table 2).…”
Section: Scn5a Promoter Haplotype and Anti-arrhythmic Efficacy Of Flementioning
confidence: 99%
See 1 more Smart Citation